Evolution of repressive sequences within an enhancer contributed to morphological diversity in crucifer plants - Alessandro Popoli; Remco A. Mentink; Lisa Brombach; Nora Papadima-Karanikou; Manuel Buendia-Monreal; Mingming Fang; Manas Joshi; Saiko Yoshida; Stefan Laurent; Peter Huijser; Miltos Tsiantis (Proceedings of the National Academy of Sciences, 2025)
Cis -regulatory sequences, such as enhancers, play a crucial role in morphological evolution, but how their diversification leads to evolution of novel expression patterns that underpin diversity is still poorly understood. Recent work suggests that the function of enhancers is influenced by their genomic sequence context more than previously thought, further complicating our understanding of their contribution to diversity. To address these issues, we investigated the regulation of the RCO homeobox gene, which contributed to the evolution of complex leaves following its tandem duplication from LMI1 . By characterizing seventeen regulatory alleles at the LMI1 / RCO locus that we generated by genome editing, we found that the evolved RCO enhancer is subject to pronounced negative regulation that helps delimit the RCO expression domain. While the LMI1 enhancer was strictly required for LMI1 gene expression, the same was not true for the RCO enhancer, which caused only partial loss of function when deleted. We mapped both positively and negatively acting sequences within the RCO enhancer, validated them in reporter gene assays and showed that a repressive sequence arose in association with a nested duplication within the evolved RCO enhancer. This repressive sequence played a key role in shaping the specific RCO expression domain that underlies its role in leaf complexity, and we provide evidence that it helped to prevent potential pleiotropic effects arising from evolutionary diversification or RCO expression. Our findings highlight the regulatory features of a diversity-linked enhancer and show that the evolution of repressive sequences is a powerful force in regulatory evolution.